Pengaruh Model Pembelajaran Kooperatif Think Pair Share Terhadap Hasil Belajar Siswa Pada Materi KPK Dan FPB Di Kelas IV SD Negeri 1 Mata Ie Aceh Besar - Zubaidah zubaidah; Monawati Monawati; Ahadin Ahadin (Universitas Syiah Kuala, 2022)
This study aims to determine the significant effect of the Think Pair Share model on student learning outcomes on the KPK and FPB material in class IV SDN 1 Mata Ie Aceh Besar. The hypothesis in this study is that there is a significant effect of the Think Pair Share model on student learning outcomes on the KPK and FBP material in class IV SDN 1 Mata Ie. This research approach is a quantitative approach, a quasi-experimental type of research with a One Group Pretest Posttest Design. This research was conducted at SD Negeri 1 Mata Ie. Sampling with saturated sampling technique and the samples in this study were all fourth-grade students of SDN 1 Mata Ie. Data collection techniques using tests, namely pretest and posttest. And the data analysis technique used a t-test at a significant level = 0.05. From the analysis of the data, it was obtained that thitunng ttable = 10.86 1.70. Based on the criteria for testing the hypothesis, it was found that Ho was rejected and H1 was accepted. So the conclusion in this study is that there is a significant effect of the Think Pair Share cooperative learning model on student learning outcomes on the material for KPK and FPB in grade IV SD Negeri 1 Mata Ie Aceh Besar.